The use of geochemical ratios in groundwater quality assessment: the case of the Thriassion Plain, Attica, Greece - Makri, Panayota; Hermides, Dimitrios; Psychogiou, Maria; Ermidou, Aikaterini (Bulletin of the Geological Society of Greece, 2019)
This paper is an effort to assess the groundwater quality and the geochemical processes mainly using the Chadha’s diagram which classifies natural waters and documents the Piper and extended Durov diagrams. Chadha’s diagram is a useful tool to interpret groundwater geochemical processes because it is produced by simple spreadsheets excel files. The example of hydrochemical analyses were given from groundwater samples of the Thriassion Plain. To attend our objective, 38 groundwater samples were collected. Hydrochemical sections, XY diagrams, distribution maps of ionic ratios as well as the Gibbs diagrams were used to identify origin of salinity and the hydrogeochemical processes that have taken place. The Gibbs diagrams have shown that evapotranspiration (ET) and rock-water interaction play an important role to the increase of groundwater salinity. The interpretation of Chadha diagram highlights that the stratigraphic factors and especially the clay strata occurrence have isolated fresh groundwater from seawater. The abundant occurrence of clay deposits to the depth of the plain work as barriers to direct seawater intrusion. Good quality groundwater identified confirms the important role of clay strata. Reverse cation exchange, is the predominant geochemical process in the Thriassion Plain aquifers, whereas evapotranspiration (ET) and rock-water interaction play an important role to the increase of groundwater salinity.